Status of Joint Forest Management in Tripura - Ray, P. N. (Indian Forester, 2000)
The Joint Forest Management programme was initiated in Tripura in December, 1991 and since then there has been reasonable progress in involving the people living around the forests to protect and improve the forests and in their share the benefits therefrom. It was at first initiated in Melaghar, West Tripura District and resulted in turming the barren lands into verdant forests with protection made available by Forest Protection and Regeneration Committees. Upto Dec. 1999, 165 such committees have been formed which protect 18,566 ha of forest land. A few microplans bave been prepared which intend to provide aided natural regeneration. Plantation of bamboo and other species, underplanting of canes, plants of medicinal value etc. have been undertaken Benefits have come as bamboos fuelwood, honey, minor forest produce, leaves etc. although the programme is still in its infancy. The committees formed are vulnerable as they have no force of law. Moreover forest produce is required to be cultivated to increase income of the members of the committees, but there are no such plans so far. The constitution and the byelaws of the committees are yet to be framed. Forest offences in such managed areas are not covered by laws except the Indian Forest Act. Mechanism for the distribution of benefits is still to be worked out and there is the paucity of funds for this programme. Flexibility in taking up works is also needed. Smuggling across the border is cause of concern. Coordination with other agencies is necessary because the benefits from such management are usually lower than benefits available from other agencies programmes. Territorial confusion with administrative unit exists. Law and order problems also handicap free working in the field. Such issues need to be looked into to attain success.The programme should commence from selected areas as Joint Forest Management is still evolving and neither the staff nor the people are ready to take it up everywhere. Positive benefits in selected areas are likely to enthuse all concerned. The staff should be trained in this new concept. Coordination committees should be formed at all levels and ensure participation of differentgovt. departments, professionals, NGOs and eminent persons. A network, if formed, will definitely make JFM an effective tool for forest conservation and rural development. Operational methodology should be worked out satisfactorily e.g. coordination between Panchayats and FRRCs. The Committees should also create own funds for the sustained working of the programme when govt assistance will not be available to them.